Análisis De Los Fundamentos Básicos Técnicos Del Baloncesto En El Rendimiento Deportivo De Los Estudiantes Categoría Intermedia Del Distrito Chambo - Riobamba - Brito, Karolina Janeth Cando; Cayo, Henry Rodolfo Gutierrez; Bravo, Hernán Leopoldo Ponce; Arcos, Helder Guillermo Aldas; Moreno, Orlando David Mazón (European Scientific Journal, ESJ, 2017)
This research was carried out on student’s athletes of Circuito Educativo 06D01C02 Riobamba-Chambo, in Chimborazo province district. The main objective of this study is to know the basic technical fundamentals of basketball in the performance of students of the intermediate category. This however would be used to determine specifically the basics technical basis. It would also help to define the level of the basic technical fundamentals in order to make a proposal. The elaboration of a training plan is aimed at developing the technical basis for the intermediate category. Within the methodology, it is a quantitative and qualitative research. This is a field research because it will run in the scene where practical assessments will be applied to each one of the students. Additionally, it will be a documentary bibliographical mode. It will be exploratory and correlational, and would take into account the population and sample which comprises of 6 coaches, 10 monitors, and 75 students of the category. The sample was under direct observation technique. As an instrument, the survey and a closed questionnaire was applied. Later on, the processing and tabulation alternative hypothesis was accepted. It was expressed as conclusions that the basic technical foundations in this category are determined by the work of dribbling, shooting ring tray, chest pass, and defense as predominant elements. It appears that the level of the basic technical fundamentals on student is regular, which is due to inadequate training and poor methods in the teaching process.